2017
DOI: 10.1038/ctg.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between IGF-1 Levels and the Histologic Severity of Nonalcoholic Fatty Liver Disease

Abstract: Objectives:The mechanisms responsible for the development of nonalcoholic fatty liver disease (NAFLD) and progression to nonalcoholic steatohepatitis (NASH) are incompletely understood. Growing evidence suggests that growth hormone (GH) and insulin-like growth factor-1 (IGF-1) may have roles in the development and progression of NAFLD. We hypothesized that lower serum IGF-1 levels would be associated with increased liver fat accumulation, inflammation, and fibrosis in a group of meticulously phenotyped obese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 63 publications
3
43
1
2
Order By: Relevance
“…In contrast, Sumida et al 26 investigated the SDS of IGF-1 by age and sex in 199 NAFLD patients, and showed that the IGF-1 SDS decreased significantly with increasing lobular inflammation and fibrosis, and showed in the multivariate logistic regression analysis the significant association between the IGF-1 SDS values and the severity of NAFLD (NASH vs NAFL or fibrosis stage 0-2 vs 3-4) after adjusting for age, sex and insulin resistance. Additionally, Dichtel et al 32 examined 21 controls with no steatosis, lobular inflammation or fibrosis and 121 NAFLD patients, and showed that IGF-1 was lower in individuals with lobular inflammation, hepatocyte ballooning, higher fibrosis stages (stage 2-4 vs 0-1) and NASH; all factors examined remained significant after controlling for age, BMI and the diagnosis of diabetes. However, these studies did not examine the relationship between IGF-1 and liver fibrosis among type 2 diabetes mellitus, which are high-risk groups of advanced liver disease; hence, this was our primary outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sumida et al 26 investigated the SDS of IGF-1 by age and sex in 199 NAFLD patients, and showed that the IGF-1 SDS decreased significantly with increasing lobular inflammation and fibrosis, and showed in the multivariate logistic regression analysis the significant association between the IGF-1 SDS values and the severity of NAFLD (NASH vs NAFL or fibrosis stage 0-2 vs 3-4) after adjusting for age, sex and insulin resistance. Additionally, Dichtel et al 32 examined 21 controls with no steatosis, lobular inflammation or fibrosis and 121 NAFLD patients, and showed that IGF-1 was lower in individuals with lobular inflammation, hepatocyte ballooning, higher fibrosis stages (stage 2-4 vs 0-1) and NASH; all factors examined remained significant after controlling for age, BMI and the diagnosis of diabetes. However, these studies did not examine the relationship between IGF-1 and liver fibrosis among type 2 diabetes mellitus, which are high-risk groups of advanced liver disease; hence, this was our primary outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…22 Indeed, lower GH concentrations have been reported in human studies with participants diagnosed with NAFLD. 25,26 A recent study showed hepatic steatosis (as assessed by a surrogate marker, the hepatic steatosis index) to be related to insulin resistance and the reduction of IGF-1 and GH levels; after 12 months of follow-up, improvements to insulin sensitivity paralleled reductions of hepatic steatosis. 25,26 A recent study showed hepatic steatosis (as assessed by a surrogate marker, the hepatic steatosis index) to be related to insulin resistance and the reduction of IGF-1 and GH levels; after 12 months of follow-up, improvements to insulin sensitivity paralleled reductions of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Moreover, low serum IGF-1 concentrations have also been associated with NAFLD and it has been suggested that hepatic insulin resistance modulates hepatic GH production and thus IGF-1 concentrations. 25,26 A recent study showed hepatic steatosis (as assessed by a surrogate marker, the hepatic steatosis index) to be related to insulin resistance and the reduction of IGF-1 and GH levels; after 12 months of follow-up, improvements to insulin sensitivity paralleled reductions of hepatic steatosis. 20 The observed risk with GH and IGF-1 deficiencies would imply that treated patients with acromegaly might be prone to develop NAFLD, because treatment does, in some cases, lead to the development of GH deficiency, as illustrated in a recently published case study.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in GH, IGF‐1 and insulin concentrations during adolescence ensure anabolism and thereby protect against steatosis. Circulating GH and IGF‐1 levels are lower in NAFLD patients than in controls . Patients with GH deficiency have an increased NAFLD prevalence .…”
Section: Paediatric Nafldmentioning
confidence: 99%
“…Circulating GH and IGF-1 levels are lower in NAFLD patients than in controls. 72,73 Patients with GH deficiency have an increased NAFLD prevalence. 72 Moreover, GH secretion is reduced in obesity, 74 without a proportional decrease in IGF-1 concentrations, 70 maintaining a negative feedback loop for GH.…”
Section: Growth (Anabolism)mentioning
confidence: 99%